(untitled) (Metallurgy and Foundry Engineering, 2014)
The aim of the work is to study the ability and potential of glass formation in Ni-Fe-Cu-P alloys. A series of alloys were produced in arc furnace (i.e. Ni70Fe5Cu5P20, Ni60Fe10Cu10P20, Ni50Fe15Cu15P20, Ni40Fe20Cu20P20, Ni30Fe25Cu25P20, Ni20Fe30Cu30P20). The primary microstructure of the ingots was studied. The ribbons in as-melt-spun state were characterized by X-ray diffraction (XRD). The Ni70Fe5Cu5P20, Ni60Fe10Cu10P20 melt-spun alloys were found to be amorphous. For higher copper and iron concentrations crystalline structure was obtained after melt spinning. This correlated with the tendency for the formation of the Fe-based phases enriched in P and Cu-based poorly alloyed phases which resulted in formation of crystalline microstructure in melt-spun ribbons. For higher concentration of Fe and Cu, microstructures of the alloys contained constituents resultant from tendency for separation in the liquid state. It is observed that formation of the crystalline melt-spun ribbons is caused by attraction of phosphorus by iron and formation of copper-based fcc phase.